Sensitivity analysis of solutions for a system of generalized parametric nonlinear quasivariational inequalities - Zeqing Liu; Beibei Zhu; Shin Min Kang; Gwang Il Kim (International Journal of Mathematics and Mathematical Sciences)
A new class of system of generalized parametric nonlinear quasivariational inequalities involving various classes of mappings is introduced and studied. With the properties of maximal monotone mappings, the equivalence between the class of system of generalized parametric nonlinear quasivariational inequalities and a class of fixed point problems is proved and an iterative algorithm with errors is constructed. A few existence and uniqueness results and sensitivity analysis of solutions are also established for the system of generalized nonlinear parametric quasivariational inequalities and some convergence results of iterative sequence generated by the algorithm with errors are proved.